Necessity of epicardial ablation for ventricular tachycardia after sequential endocardial approach. (1st March 2015) - Sultan, Arian; Lüker, Jakob; Hoffmann, Boris; Servatius, Helge; Aydin, Ali; Nührich, Jana; Akbulak, Özge; Schreiber, Doreen; Schäffer, Benjamin; Rostock, Thomas; Willems, Stephan; Steven, Daniel
Abstract: Background: Catheter ablation (CA) of ventricular tachycardia (VT) is an important treatment option in patients with structural heart disease (SHD) and implantable cardioverter defibrillator (ICD). A subset of patients requires epicardial CA for VT. Objective: The purpose of the study was to assess the significance of epicardial CA in these patients after a systematic sequential endocardial approach. Methods: Between January 2009 and October 2012 CA for VT was analyzed. A sequential CA approach guided by earliest ventricular activation, pacemap, entrainment and stimulus to QRS-interval analysis was used. Acute CA success was assessed by programmed ventricular stimulation. ICD interrogation and 24 h-Holter ECG were used to evaluate long-term success. Results: One hundred sixty VT ablation procedures in 126 consecutive patients (114 men; age 65 ± 12 years) were performed. Endocardial CA succeeded in 250 (94%) out of 265 treated VT. For 15 (6%) VT an additional epicardial CA was performed and succeeded in 9 of these 15 VT. Long-term FU (25 ± 18.2 month) showed freedom of VT in 104 pts (82%) after 1.2 ± 0.5 procedures, 11 (9%) suffered from repeated ICD shocks and 11 (9%) died due to worsening of heart failure. Conclusions: Despite a heterogenic substrate for VT in SHD, endocardial CA alone results in high acute success rates. In this study additional epicardial CA following a sequential endocardial mapping and CA approach was performed in 6% of VT. Thus, due to possible complications epicardial CA should only be considered if endocardial CA fails. Highlights: Necessity of epicardial ablation after a thorough endocardial approach by a sequential ablation protocol in SHD. High acute and long-term success rates by sole endocardial ablation regarding VT freedom with a maximum risk reduction. Significance of conventional mapping and stim-QRS interval for determination of ablation sites, termination and success.